Prevalence of coronary artery calcification in Japanese patients with psoriasis: A close correlation with bilateral diagonal earlobe creases - Honma, Masaru; Shibuya, Takashi; Iwasaki, Takeshi; Iinuma, Shin; Takahashi, Noriyoshi; Kishibe, Mari; Minami‐Hori, Masako; Ishida‐Yamamoto, Akemi (Journal of dermatology, 2017)
Psoriasis is a multifactorial inflammatory disorder, in which the inflammation affects not only the skin but also the other internal organs, and can induce cardiovascular and cerebrovascular involvements. However, few predictive factors of cardiovascular diseases have been clarified in patients with psoriasis. This study was performed to verify whether diagonal earlobe creases (ELC) can reflect the hidden comorbidities in Japanese psoriatic patients. Prevalence and subtypes of ELC were analyzed in patients with psoriatic and with non‐psoriatic skin diseases, and the correlation with coronary artery calcification (CAC) or fatty liver (FL) detected by computed tomography. Prevalence of CAC was approximately twice higher than data of a Japanese resident‐based study previously reported. Generally, prevalence of ELC in a psoriatic group and mean age of psoriatic groups accompanied by ELC were higher and younger than those of a non‐psoriatic skin disease group, respectively. Statistically significant differences were detected in the mean age of total or male subjects accompanied by bilateral ELC with complete and incomplete length. Bilateralism of ELC was closely correlated with prevalence of CAC and CAC on multiple branches in psoriatic patients (P = 6.6e‐6 and odds ratio [OR] = 14.1, P = 0.00884 and OR = 10.7, respectively), but not with that of FL. On the contrary, body mass index of more than 25 was closely correlated with prevalence of FL, but not that of CAC. Comorbidities of psoriatic patients are frequently unnoticed. ELC, an apparatus‐related feature, can be a useful predictive factor for hidden coronary artery involvements in psoriatic patients.